PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN KELOMPOK JAKARTA ISLAMIC INDEX - Wardana, Guntur Kusuma; Gumanti, Tatang Ary; Utami, Elok Sri (IQTISHODUNA, 2015)
The purpose of this research is to analyse the influence of financial performance on returns a stockslisted in Jakarta Islamic Index. The populations in this research are all companies listed on the Jakarta IslamicIndex (JII) 2012 to 2013. The data were analysed by using method criteria a purposive sampling generate a totalof 20 companies. Multiple regression analysis results show that Price Earnings Ratio effect CumulativeAbnormal Returns, while the Net Profit Margin, Price to Book Value and Current Ratio do not influence onCumulative Abnormal Return.